Idiopathic intraosseous ganglion of the distal tibia in a young adult male: A case report with review of literature - Ahmad, Javed; Patel, Brijmohan; Ayaz, Ahmad; Shrivastava, Vivek Kumar; Singh, Mohit Kumar (Asian Journal of Medical Sciences, 2023)
Intraosseous ganglion is a benign cystic bony lesion containing viscous and mucinous gelatinous material, which is usually seen in middle-aged individuals. It is similar to soft-tissue ganglion cysts present in other parts of the body. We, hereby, report a rare case of idiopathic intraosseous ganglion of the tibia in a young adult who presented with chronic pain in his lower leg. The patient was subjected to X-ray and MRI investigations and managed by excisional curettage of the lesion and histopathological examination. On histopathology, the diagnosis of intraosseous ganglion was confirmed. On 2-year follow-up, the patient was doing well without any complication and recurrence. This report describes the diagnosis and successful management of intraosseous ganglion at a very rare site in a young individual. More in-depth studies are required to understand the predisposing factors, underlying pathology, early diagnosis, and management of this lesion.